Argentine rice and sorghum have promissory potential as service crops for biological inhibition of nitrification - Vassallo, Gianina; Carrizo, Manuel; Delaporte Quintana, Paola Adriana Georgina; Zarate, M.; Ducci, María Antonella; Perez Brandan, Carolina; Acreche, Martin Moises; Chalco Vera, Jorge Elías (Asociación Argentina Ciencia del Suelo, 2024)
Agriculture faces the challenge of regulating soil nitrification which promotes the loss of applied nitrogen (N) as, for example, nitrous oxide (N2O) emissions. Biological inhibition of nitrification (BIN), a process that suppresses soil nitrifying activity by the release of root exudates from some plants, is a desirable characteristic that can improve N utilization and nitrogen use efficiency (NUE) and mitigate N losses. We aimed to assess the potential BIN of commercial varieties of rice and sorghum to screen the best of them and evaluate their impact on ammonium and nitrite oxidant bacteria. We conducted an experiment to determine the potential nitrification rates in soil with different rice and sorghum varieties. We planted seeds in pots, took soil samples after six weeks, and incubated them for 16 days. We extracted mineral N at different time intervals and calculated potential soil nitrification rates. We also estimated the number of cultivable nitrifiers using the Most Probable Number technique. The nitrification rates varied based on the time period and treatment. Two commercial varieties of rice and sorghum potentially have the ability to inhibit soil nitrification. The MPN method showed that the BIN capacity of rice targeted the nitrite-oxidizing bacteria (NOB) community up to 10 days from N addition. This could probably increase N2O emissions. Thus, comprehensive field studies are necessary to determine the net nitrogen loss mitigation potential of rice and sorghum varieties.